Exploring of Ethnomathematics in the Local Culture of North Karawang Coastal Fishermen for Elementary School Mathematics - Diah Pitaloka; Indrie Noor Aini (Edumatika, 2025)
This research aims to explore the activities of fishermen on the coast of Sungai Buntu Beach, Karawang, that contain mathematical concepts, and to map them into the learning outcomes of phases A–C at the primary school level. A qualitative approach with an ethnographic design was used, through observation, interviews, and documentation. The data were then analysed with data reduction, presentation, and conclusion drawing, and their validity was tested through triangulation. The results show that fish trading activities contain number concepts; calculating the catch in a basket reflects algebra through variables and simple equations; the salting and weighing of fish emphasise measurement, proportionality, and capacity; the shapes of boats, nets, baskets, drying racks, and fish crates demonstrate the application of geometric concepts in 2D and 3D shapes; and seasonal catch patterns, trading transactions, and the salting of dried fish provide a context for data analysis and probability. These findings affirm that the cultural practices of fishermen in the North Karawang coastal area, particularly those in Sungai Buntu Beach can be used as an authentic source for contextual, relevant, and meaningful mathematics learning, and are also applicable to other coastal regions with similar cultural characteristics such as the North Coast of West Java, supporting the development of local culture-based teaching materials to enhance students' motivation, understanding, and learning outcomes.